2019
DOI: 10.15845/voices.v19i1.2731
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Investigating Research Design Feasibility Using Pre-post Measures to Test the Effect of Music Therapy in Psychiatry with People Diagnosed with Personality Disorders

Abstract: Introduction: The objectives of the pilot study were (a) to investigate the feasibility of the research design (referral procedure, data collection procedure, measurement tools, and treatment doses/frequency); (b) to develop and evaluate the PROMT treatment manual; and (c) to test the use of flexible and or multiple interventions as part of the treatment options. Findings from this investigation aim to prepare for a future outcome study of music therapy treatments for patients with personality disorders, that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This type of research design has commonly been used in music therapy to assess effectiveness of the intervention (e.g. Oldfield et al, 2003, Hannibal et al, 2019). In this study, the changes are compared for the two interventions.…”
Section: Quantitative Results and Statistical Analysismentioning
confidence: 99%
“…This type of research design has commonly been used in music therapy to assess effectiveness of the intervention (e.g. Oldfield et al, 2003, Hannibal et al, 2019). In this study, the changes are compared for the two interventions.…”
Section: Quantitative Results and Statistical Analysismentioning
confidence: 99%
“…Music has been used in conjunction with mentalization as a complementary therapy for patients with BPD [16]. They discuss a pilot study using a theoretical model integrating Mentalization-Based-Treatment (MBP) into music therapy.…”
Section: Music Therapymentioning
confidence: 99%
“…MT is increasingly recognized as a promising treatment for people with PD (Hannibal, 2016; Odell‐Miller, 2011/2016; Plit [2012] in Foubert et al, 2020; Strehlow & Hannibal, 2019; Strehlow & Lindner, 2016) and it is mentioned in the Dutch multidisciplinary treatment guidelines for PD (FMS, Federatie Medisch Specialisten, 2022; Haeyen, 2022). Evidence of its efficacy remains limited, however, due to small sample sizes and methodological limitations.…”
Section: Introductionmentioning
confidence: 99%
“…The results, based on an existing data set, were similar to those of a group that received art therapy: reduced symptoms and increased functioning. At the same time, the authors reported that “for some clients MT was challenging” (Hannibal, 2016, p. 47). Hannibal et al (2019) used a pre–post design to assess process‐oriented MT ( N = 4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation